A case report: cccDNA and pgRNA remain positive in liver tissue in a chronic hepatitis B patient with functional cure - Xu, Wenxiong; Luo, Qiumin; Zhang, Yeqiong; Xie, Chan; Peng, Liang (Frontiers in Medicine, 2024)
Hepatitis B surface antigen (HBsAg) seroclearance is recommended as the ideal endpoint for nucleos(t)ide analog (NA) treatments. Functional cure of chronic hepatitis B (CHB) is defined as having undetectable serum hepatitis B virus (HBV) deoxyribonucleic acid and serum HBsAg. We report a functional cure case of CHB with a family history of hepatocellular carcinoma (HCC) after long-term NA therapy. Despite achieving functional cure for over 7 years, both HBV covalently closed circular deoxyribonucleic acid (cccDNA) and pregenomic ribonucleic acid (pgRNA) remain positive in the liver tissue of the patient, indicating that a sterilizing cure has not been achieved. This case highlights the importance of active surveillance of HBV cccDNA and pgRNA for sterilizing the cure and risk of HCC.